Good and Bad Tongues: Iconographic Clarifications of Talking Signs (II) - Sigüenza Martín, Raquel (Eikón / Imago, 2014)
After analysing some negative aspects and bad uses of the tongue as the organ of speech, we will try to study the “good tongues” along the following lines. They are apparently an inferior matter for art and emblems than the “bad tongues”. This article is divided according to the two main capabilities of the tongue: silence and speech. There is a simultaneous appreciation of silence and eloquence, if used at the right time, which will be studied in another section. Finally, we dedicate some lines to several tongue representations without positive or negative connotations about their usage.